Analysing the effects of brazing inconel alloy - Dain Ibrahim Rahman (2018)
In this report, we would be studying the optimisation of brazing with Nickel based filler (AMS4777) on Inconel 718 under atmospheric condition. This report will also be focusing on the effects of tensile strength and its microstructure, due to variations in temperature and soak time during brazing.